Seismic behaviour investigation of a cable-stayed bridge with hybrid passive control system / Ahad Javanmardi - Ahad , Javanmardi (2019)
The construction of cable-stayed bridges has been increasing worldwide owing to their characteristics, such as appealing aesthetics, longer span length and lightweight that have high logistic and economic value. However, cable-stayed bridges are also associated with low structural damping and longer fundamental periods, which make them highly vulnerable to large amplitude oscillation during seismic events. Consequently, studying the seismic response and protection of cable-stayed bridges from seismic loading is essential. This research studies the seismic behavior and protection of an existing steel cable-stayed bridge located in a high-risk seismic zone in Canada. This bridge was chosen based on the availability of detailing data and experimental results. For instance, earthquake-induced pounding caused structural damages and also one anchorage plate in the bridge support failed due to the Saguenay earthquake in 1988. The main objective of this research is thus to enhance the seismic performance of the cable-stayed bridge by means of a hybrid passive control system, which is a combination of seismic isolator and a novel metallic damper to minimize future damage that may be induced by earthquakes. Initially, the cable-stayed bridge is rigorously modeled in three dimensions and validated with experimental results. Then, different seismic isolation retrofitting cases are defined and isolation systems are designed for each case accordingly. Thereafter, the new metal damper, called the hexagonal honeycomb steel damper, is proposed and developed experimentally and numerically to determine its behavior and characteristics. Finally, the proposed damper is designed and modelled for the fully isolated cable-stayed bridge. The seismic response of each cable-stayed bridge retrofitting case is evaluated through a series of nonlinear time-history analysis. The comparative analysis indicates that the partial seismic isolation of the cable-stayed bridge enhanced its seismic behavior in one direction only. In order to enhance the seismic performance of the cable-stayed bridge in both directions, the isolation system should be utilized at the end supports, as well as the deck-tower connection or base of the tower. The global and local seismic responses of the fully isolated cable-stayed bridge significantly improved, compared to the non-isolated bridge. However, the seismic displacement of the superstructure increased in the fully isolated bridge. The result of quasi-static cyclic test on the proposed damper showed that, the damper exhibited low yield displacement, excellent strength and ductility, and stable hysteretic behavior with high energy absorbing capability. Consequently, implementation of the metallic damper in the fully isolated bridge caused a significant reduction in superstructure displacement under earthquake loading, which also eliminated the earthquake-induced pounding effect at the bridge ends with adjacent abutments. The hybrid passive control system is beneficial in the protection of cable-stayed bridges in high-risk seismic zones. The system reduces the seismic demands on the structure and mitigates the seismic displacement of the superstructure as well as the likelihood of earthquake-induced pounding in the bridge.